2020
DOI: 10.4269/ajtmh.20-0371
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Abnormalities Detected by Point-of-Care Lung Ultrasound in Symptomatic COVID-19 Patients: Systematic Review and Meta-Analysis

Abstract: The COVID-19 pandemic has resulted in significant morbidity, mortality, and strained healthcare systems worldwide. Thus, a search for modalities that can expedite and improve the diagnosis and management of this entity is underway. Recent data suggested the utility of lung ultrasound (LUS) in the diagnosis of COVID-19 by detecting an interstitial pattern (B-pattern). Hence, we aimed to pool the proportion of various reported lung abnormalities detected by LUS in symptomatic COVID-19 patients. We conducted a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 29 publications
6
59
0
3
Order By: Relevance
“…Point-of-care ultrasound (POCUS) has proven to be effective in COVID-19 diagnosis. 15 Although the treating clinicians can use POCUS for diagnosis and follow-up, they can still use it to look for signs deep venous thrombosis (veins non-compressibility) and pneumothorax (barcode sign, and absence of lung sliding). 16 This modality can be useful in resourceful and resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) has proven to be effective in COVID-19 diagnosis. 15 Although the treating clinicians can use POCUS for diagnosis and follow-up, they can still use it to look for signs deep venous thrombosis (veins non-compressibility) and pneumothorax (barcode sign, and absence of lung sliding). 16 This modality can be useful in resourceful and resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…In another letter, the same author discusses the significance of finding evidence of interstitial pneumonia evidenced by the B-pattern in the diagnosis of COVID-19; nonetheless, the author acknowledges lack of specificity of this finding (2). In a recent meta-analysis of seven studies (122 patients), we found that the B-pattern is consistently prevalent (97%, 95% CI: 0.94À1.00 I 2 0%) among COVID-19 symptomatic patients (3). Additionally, we found 70% and 54% frequency of finding pleural line abnormalities and pleural thickening, respectively, although they were heterogeneous among constituent studies.…”
Section: Dear Editormentioning
confidence: 75%
“…A recent meta analysis [14] showed that the majority of COVID-19 patients have pathological ndings at LUS. The most frequent is interstitial involvement as demonstrated by a B-lines pattern ( gure 3), followed by pleural thickening and irregularities, consolidations and seldomly pleural effusions.…”
Section: Lung Ultrasoundmentioning
confidence: 99%